Structural, thermal and optical absorption features of heavy metal oxides doped tellurite rich glasses - Kaky, Kawa M.; Lakshminarayana, G.; Baki, S. O.; Kityk, I. V.; Taufiq-Yap, Y. H.; Mahdi, M. A. (Elsevier, 2017)
In order to improve tellurite glass stability to be applicable for optical fiber amplifier applications, glasses with the composition of (70 − x)TeO2. (10)ZnO. (10)WO3. (5)Na2O. (5)TiO2. (x)Bi2O3 (x = 1, 2, 3, 4, and 5 mol%) have been produced and characterized using the related methods. Structural properties were investigated using X-ray diffraction (XRD) which confirms the non-crystalline structure and scanning electron microscopy (SEM) micrographs also confirm the XRD results. The energy dispersive X-ray (EDX) analysis profiles show that all the mentioned elements are present in the prepared glasses. Following the IR spectra, all the tellurium bonds such as stretching vibrations of TeO4 tbp and TeO3/TeO3+1 unit are revealed. Raman spectra confirm the presence of different functional groups, actually, it shows bands mainly in four spectral regions: R1 (65–150) cm−1, R2 (280–550) cm−1, R3 (880–950) cm−1 and R4 (916–926) cm−1 and the identified bands are assigned to respective molecular groups. The thermal study was carried out using Differential scanning calorimetry (DSC) which indicates good thermal stability of the synthesized glasses with increasing Bi concentration. From the optical absorption spectra, we evaluated cut-off edge wavelengths and found increasing cutoff wavelength with an increase in Bi2O3 concentration. In the UV–Visible region, optical band gap energy and allowed transitions were investigated using three methods; direct, indirect, and absorption spectrum fitting (ASF), and band gaps from indirect and ASF were matched.